Prevention of the Inflammatory Complications - Tymofieiev, O. O.; Fesenko, Ye. I.; Ushko, N. O.; Yarifa, M. O. (Actual Dentistry, 2020)
Summary. Conducting of prophylactic antibiotic therapy in patient after surgical interventions in oral and maxillofacial surgery reduces the incidence of postoperative infectious complications. The general questions of prophylaxis, oral microflora are considered. Recommendations on the antibiotic prophylaxis in oral and maxillofacial surgery are given.